Gaze-Based Assessments of Vigilance and Avoidance in Social Anxiety: a Review - Chen, N.; Clarke, Patrick (2017)
© 2017, Springer Science+Business Media, LLC. Purpose of Review: A broad base of research has sought to identify the biases in selective attention which characterize social anxiety, with the emergent use of eye tracking-based methods. This article seeks to provide a review of eye tracking studies examining selective attention biases in social anxiety. Recent Findings: Across a number of contexts, social anxiety may be associated with a mix of both vigilant and avoidant patterns of attention with respect to the processing of emotional social stimuli. Socially anxious individuals may additionally avoid maintaining eye contact and may exhibit a generalized vigilance via hyperscanning of their environment. Summary: The findings highlight the utility of eye tracking methods for increasing understanding of the gaze-based biases which characterize social anxiety disorder, with promising avenues for future research.